Spatially resolved measurements of RF accelerated deuterons at JET. (16th February 2021) - Sahlberg, A.; Eriksson, J.; Conroy, S.; Ericsson, G.; Nocente, M.; Kazakov, Ye.O.; JET Contributors,
Abstract: An understanding of fast (supra-thermal) ion behavior is of great importance in tokamak physics and is a subject studied from both theoretical and experimental perspectives. This paper investigates the spatial energy and density distributions of RF accelerated deuterons using the neutron camera at the tokamak JET. Using the 19 liquid scintillator detectors available in the neutron camera system, we obtain spatial information that cannot be accessed with a single sightline. We present a spectroscopic analysis method in which a spatially resolved model of the fast ion distribution is fitted to the pulse height spectra from all 19 detectors simultaneously. The fast ion distribution is parameterized in such a way that the density, energy, and pitch-angle parts are uncoupled. The energy part is composed of a Maxwellian distribution, characterized by an 'RF tail temperature, ' and the spatial dependence is modeled as a two-dimensional Gaussian distribution on the poloidal plane of the tokamak. From this parameterized model, we can calculate the spectrum of fusion born neutrons originating from reactions involving RF accelerated deuterons, and by fitting this model to the measured neutron camera pulse height spectra, we obtain an estimate of the spatially resolved distribution of the fast deuterons. The method has been applied to three JET pulses using different RF heating schemes and is shown to identify several features of the fast ion distribution produced in the various scenarios. Hence, this method is able to provide quantitative information about the fast ion distribution resulting from different heating schemes, and can also be useful, e.g., to validate simulation results from RF modeling codes.